RESEARCH ON THE CHEMICAL COMPOSITION OF SNOW OF ALMATY CITY - Medeuova Galiya Zhumakanovna; Zhailybay Kelis Nurmashuly; Kishibayev Kazhmukhan (Academic Journal of Physical and Chemical Sciences, 2020)
The article shows that according to the data of Kazgidromet from 2014-2015 years, Almaty takes one of the first places among the cities of Kazakhstan in terms of air pollution. Currently, Almaty is one of the 25 cities in the world in terms of air pollution. The main source of air pollution is harmful substances coming out of the exhaust pipes of vehicles. According to data from the traffic police, 540,000 vehicles have been registered in Almaty. Their number is increasing to 40,000 annually. Every day 250 thousand cars are driven into and out of the city. Polluting substances appear everywhere, their harmful influence on organisms of people, animals and plants is various: they increase metal corrosion, damage respiratory tract of population and animals, have negative influence on vegetation cover. During windless days they accumulate as smoke (smog) over the city of Almaty.